Performance study of Reference Height Control Algorithm for Tripod Hopping Robot - Anuar , Mohamed Kassim; Abas, Norafizah; Mohd Aras, Mohd Shahrieel; Ab Rashid, Mohd Zamzuri (Praise Worthy Prize, 2013)

(untitled)
Central Pattern Generator(CPG) algorithm enables to produce rhythmic patterned outputs where this neural networks underlie the production of most rhythmic motor patterns. In this paper, the generation of vertical jumping motion for tripod hopping robot by applying the Central Pattern Generator networks with reference height control algorithm in order to achieve reference height for each leg of tripod hopping robot is discussed. The proposed algorithm is designed using MATLAB/ Simulink which is consisted of maximum height detector, PI controller in the system of Central Pattern Generator (CPG). By using the proposed algorithm, the developed tripod hopping robot can achieve the reference height and maintain the hopping motion respectively. As the result, the effectiveness of proposed reference height control algorithm in order to achieve the reference height is confirmed.